Composition, Granular Structure, and Pasting Properties of Native Starch Extracted from Plectranthus edulis (Oromo dinich) Tubers. Issue 12 (1st December 2017) - Hellemans, Tom; Abera, Gifty; De Leyn, Ingrid; Van der Meeren, Paul; Dewettinck, Koen; Eeckhout, Mia; De Meulenaer, Bruno; Van Bockstaele, Filip
Abstract : Abstract: Chemical composition, granular morphology and pasting properties of native starch extracted from tubers of Plectranthus edulis were analyzed. Starch was extracted from tubers of 6 accessions collected from 4 different areas in Ethiopia. Particle size analysis (PSA) and cryo‐scanning electron microscope (cryo‐SEM) imaging were used to examine the granular morphology and visualize the starch paste, respectively. Pasting properties, water absorption, and gelation capacity were compared. A wide range was found for the amylose (14.2% to 23.9%), calcium (216 to 599), potassium (131 to 878), and phosphorus (1337 to 2090) contents (parts per million per dry matter). PSA showed a bimodal distribution containing small spherical (14.6 μm) and large ellipse‐shaped (190.4 μm) granules. Major differences were found for the pasting with peak viscosities differing from 3184 to 7312 mPa⋅s. Starch from accessions Chencha and Inuka showed a difference in packing density as clearly seen through cryo‐SEM image at 75% of the peak viscosity (PV), and the granular integrity was mainly responsible for the significant difference in their PV and breakdown. Principal component analysis revealed 2 distinct groups: native starch extracted from accessions at the Wolayta zone ( Inuka, Lofua, and Chenqoua ) and other accessions ( Jarmet, Arjo white, and Chencha ). The study revealed the potential of P. edulis starch for its application in food industries. However, the inherent variation due to environmental conditions on physicochemical properties of the starch needs further investigation. Practical Application: Plectranthus edulis is cultivated in considerable amounts throughout Ethiopia, which makes it a valuable starch source. Due to its low tendency to retrograde, it could be applied in food industry as an equivalent for the current starch sources. Moreover, the low amylose content makes it preferable for an application in refrigerated foods as this unique quality trait prevents syneresis in end products during storage. Based on the significantly higher pasting temperature of the studied P. edulis starch extracts, it can form an alternative for potato starch, which is less suitable for its use in pasteurized foods.